Human dimensions in flood risk management: Exploring risk perception and climate change considerations among engineers in the US - Mohammad Pourmatin; Elham Ajorlou; Ali Farhadzadeh; Majid Ghayoomi; Elizabeth Hewitt (Progress in Disaster Science)
Due to an increase in natural hazards, the cost of physical damage to local infrastructure has grown significantly. However, many vulnerabilities faced by the built environment involve human factors, which remain understudied. This study examines factors that influence how hydraulic and coastal engineers involved in U.S. flood infrastructure design perceive risk and integrate environmental and social considerations into their professional recommendations. A survey was conducted of U.S.-based civil engineers specializing in flood infrastructure design to assess factors influencing their design-related judgments. Using various statistical analyses, this study identifies key predictors shaping engineers' engagement with risk and climate. Results show that engineers with liberal political orientations are more likely to incorporate climate change impacts into designs, and household income is negatively associated with risk-aversion attitudes. Engineers with limited work experience report more influence from peers, and dissatisfaction with engineering education is a strong predictor of reliance on personal attitudes when facing uncertainty. While engineers are not the final decision-makers, these findings highlight their crucial role as intermediaries who shape how risk is framed and which options are presented to agencies and clients. These findings offer novel contributions merging social science with engineering and inform how decision-makers can enhance flood risk management.